Blockchain for IoT Security and Privacy: A Case Study of a Smart House - Mrs.G.Swetha, Mr.K.Narender Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Security and privacy for Internet of Things (IoT) networks continue to be a significant concern, primarily because of the vast scale and scattered nature of IoT networks. Although blockchain-based systems offer decentralised security and anonymity, they come with a high energy, latency, and processing overhead, making them unsuitable for the majority of IoT devices with limited resources. In our earlier work, we introduced a lightweight instantiation of a BC that was specifically designed for usage in the Internet of Things (IoT) by getting rid of the Proof of Work (POW) and the idea of coins. Our strategy, which was demonstrated in a smart home environment, has three key tiers: cloud storage, overlay, and smart house. In this essay, we go into more detail and define the different essential elements and features of the smart home tier. Every smart home has a "miner," which is a high-resource, constantly online device in charge of managing all communication both inside and outside the house. The miner also keeps a private and secure BC that is employed for monitoring and managing conversations. By carefully examining its security in relation to the core security objectives of confidentiality, integrity, and availability, we demonstrate the security of our proposed BC-based smart home system. Finally, we demonstrate simulation findings to demonstrate that our approach's overheads (in terms of traffic, processing time, and energy usage) are negligible compared to the security and privacy improvements it provides